2022
DOI: 10.3389/fpsyg.2022.796057
|View full text |Cite
|
Sign up to set email alerts
|

Invariance of the Trait Emotional Intelligence Construct Across Clinical Populations and Sociodemographic Variables

Abstract: Recent research has shown that cultural, linguistic, and sociodemographic peculiarities influence the measurement of trait emotional intelligence (trait EI). Assessing trait EI in different populations fosters cross-cultural research and expands the construct’s nomological network. In mental health, the trait EI of clinical populations has been scarcely researched. Accordingly, the present study examined the relationship between trait EI and key sociodemographic variables on Trait Emotional Intelligence Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“… Pérez-Díaz et al (2021) found scalar invariance (equal latent means) between genders in a sample of healthy subjects measured through the TEIQue. Furthermore, Pérez-Díaz et al (2022) found a metric (equal factor loading) and scalar (equal latent means) invariance in a clinical sample between men and women of the TEIQue.…”
Section: Introductionmentioning
confidence: 90%
“… Pérez-Díaz et al (2021) found scalar invariance (equal latent means) between genders in a sample of healthy subjects measured through the TEIQue. Furthermore, Pérez-Díaz et al (2022) found a metric (equal factor loading) and scalar (equal latent means) invariance in a clinical sample between men and women of the TEIQue.…”
Section: Introductionmentioning
confidence: 90%
“…Este instrumento se ha utilizado ampliamente en el contexto español en estudios tanto con muestra de estudiantes universitarios, como de docentes de distintos niveles educativos, de orientadores, e incluso con muestra clínica (e.g., Cejudo & Delgado, 2017;Laborde et al, 2016;Pérez-Díaz et al, 2022).…”
Section: El Cuestionario De Inteligencia Emocional Rasgo (Trait Emoti...unclassified
“…For the assessment of EI as a personality trait of teachers and students, we used the Spanish version (Pérez, 2003) of the TEIQue-SF [Trait Emotional Intelligence Questionnaire-Short Form] (Petrides, 2009), a questionnaire considered one of the most comprehensive, reliable and valid assessments of global EI as a set of personality dispositions that facilitate emotionally intelligent behavior (Pérez-Díaz et al, 2022;Pérez-González and Sánchez-Ruiz, 2014).…”
Section: Instrumentsmentioning
confidence: 99%